International Seminar on Nuclear War and Planetary Emergencies : (World Scientific, 2003)
Contents: This was the first of a number of seminars dealing with one of the most complex of the new challenges in the 21st century, which call for the participation of a broad range of experts. Eminent economists, decision-makers, defence specialists, political analysts and sociologists presented their views and participated in the debates. In the wake of the dramatic event of 11 September 2001, the Afghanistan war and the resurgence of terrorist acts on all the continents, a host of issues were reconsidered and the role of science and technology was reassessed. The 27th Session was primarily oriented toward the definition of the new types of confrontation, and the identification of various factors and issues that gave rise to them and global trends.The proceedings have been selected for coverage in: • Index to Scientific & Technical Proceedings (ISTP CDROM version / ISI Proceedings)• Index to Social Sciences & Humanities Proceedings® (ISSHP® / ISI Proceedings)• Index to Social Sciences & Humanities Proceedings (ISSHP CDROM version / ISI Proceedings)